Vestibular and Oculomotor Function in Children with Cerebral Palsy: A Scoping Review - Almutairi, Anwar (Semin Hear, 2018)
Cerebral palsy (CP) is a nonprogressive permanent brain injury that causes an impairment of movement and posture. This scoping review aimed to answer the following questions: (1) “What is the status of oculomotor function in children with CP?” (2) “What is the status of vestibular function (i.e., gaze stability, perception of vertical, vestibular-related balance abilities) in children with CP?” Using Arksey's and O'Malley's five-stage framework, we searched six online databases for relevant articles. The inclusion criteria were: (1) participants of the studies included individuals with CP; (2) a primary outcome in the studies was measurement of oculomotor, vestibular, and/or balance; (3) studies were published within the past 20 years; and (4) the participants in the studies were between 0 and 21 years of age. Twenty-one articles were found that described impairments in oculomotor function ( n  = 9), vestibular function ( n  = 1), and oculomotor and vestibular integration ( n  = 11) in children with CP. The evidence suggests that children with CP may have altered saccadic and smooth pursuit eye movements, abnormal saccular function, poor eye–hand coordination, and abnormal use of vestibular information for balance. Future studies should explore peripheral and central vestibular function using reliable and valid methods for this population. This scoping review demonstrated a paucity of rigorous and objective research to describe the status of oculomotor and vestibular function in children with CP. However, preliminary studies suggest that more research is warranted.